2011
DOI: 10.1136/jclinpath-2011-200345
|View full text |Cite
|
Sign up to set email alerts
|

HER2 status in unusual histological variants of gastric adenocarcinomas

Abstract: Trastuzumab has been confirmed as an additional useful therapeutic standard option for patients with HER2-positive advanced gastric cancers, and also in aggressive variants of adenocarcinomas such as HAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…According to previous studies, HER2-positivity rate was about 9-38 % [14][15][16][17][18][19]. In our current study, the overall HER2-positivity rate was 21 % in advanced and metastatic gastric cancer.…”
Section: Discussionmentioning
confidence: 50%
“…According to previous studies, HER2-positivity rate was about 9-38 % [14][15][16][17][18][19]. In our current study, the overall HER2-positivity rate was 21 % in advanced and metastatic gastric cancer.…”
Section: Discussionmentioning
confidence: 50%
“…Levels of AFP in the serum and tumor tissue are significantly high in this form of gastric cancer; however, HAC is rare, accounting for 1.3-15% of gastric cancers (9). Although there have been some previous reports about this disease (10,11), there remains a lack of understanding. HAC is discussed here with reference to the present case and published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although reported rates of HER2 overexpres- Recently, Giuffre et al reported that a markedly increased HER2 amplification was more frequent in HACS (42.9%) than that seen in tubular gastric adenocarcinomas (31.3%) [1]. This finding shows trastuzumab can be a useful therapeutic standard option not only for patients with advanced gastric cancer but also in aggressive variants like HACS.…”
Section: Hepatoid Adenocarcinomamentioning
confidence: 99%